Renal replacement therapy in sarcoidosis - Calatroni, Marta; Moroni, Gabriella; Ponticelli, Claudio (Frontiers in Medicine, 2023)
Sarcoidosis is a systemic inflammatory disease of unknown etiology. Kidney involvement in sarcoidosis may be present in up 25-30% of cases. An early diagnosis and prompt treatment with corticosteroids can improve the prognosis but rarely renal sarcoidosis can lead to kidney failure needing renal replacement therapy (RRT). Acute kidney injury (AKI) in sarcoidosis may be caused by granulomatous interstitial nephritis (GIN) or hypercalcemia. These disorders are usually clinically silent and may lead end stage renal disease (ESKD) if not diagnosed or detected too late. In patients with ESKD, dialysis and renal transplantation can offer results comparable to those observed in patients with other causes of kidney failure. Based on a review of literature, we present an overview of RRT in patients with AKI or chronic kidney disease (CKD) caused by sarcoidosis.